Critical factors influencing decision to adopt digital forensic by Malaysian law enforcement agencies: a review of PRISMA / Siti Nuur-Ila Mat Kamal, Othman Ibrahim and Mehrbakhsh Nilashi - Mat Kamal, Siti Nuur-Ila; Ibrahim, Othman; Nilashi, Mehrbakhsh (UiTM Cawangan Johor, 2019)
The technological advancement in today's era has been characterized by a proliferation of digital devices and system. This scenario is seen significant in bringing a great impact to the increasing needs of digital forensic to be recognized as a crucial tool and yet an investigative procedures in facilitating today's organizations especially the law enforcement agencies to react into the cybercrime cases that fall under their respective jurisdiction. However, in a context of a developing country, the adoption nature towards digital forensic by Malaysian law enforcement agencies is unfavorable which ultimately affects an efficient, timeliness, cost-effective, and less-impact of digital evidence investigation. The purpose of this paper is to examine the factors affecting the decision of Malaysian law enforcement agencies to adopt digital forensic. The study employed PRISMA as a reference methodology to identify the factors and developing the initial adoption model. The methodology has revealed 12 factors that influence the adoption decision of digital forensic. These factors are organized into three dimensions under the premise of TOE framework namely technological, organizational and environmental. The study is contributing by addressing the key driving factors that delineate an understanding towards the context of digital forensic as an innovation adoption at the organizational level in which further will be exploited to formulate the adoption model.